The Relationship Between Social Media Marketing, Psychological Distance, Purchase Intention And Customer Loyalty: Case Of Hypermarket Social Media Users In Indonesia - Dewanti, Retno (2015)
To date there are many hypermarkets that uses social media to manage its relationship between the customers and the company in order to increase the level of customers' loyalty towards hypermarket. This is what this research addresses. Study uses Theory of Planned Behavior. The study also focuses on the social media marketing model where it looks at the effectiveness on the usage of social media in developing the intention to purchase and the loyalty among the customers. This data is analysed using Partial Least Square (PLS). Data was collected from over 482 respondents from 20 hypermarkets which is under 4 different major areas in cities around the Jakarta Metropolitan area. Data was collected from customers who are twitter and facebook account users from the shops at the identified at the four hypermarkets. Findings indicates that social media has a positive influence on the intention to purchase. Intention to purchase was found to have a positive effect on customers' loyalty and was also found to mediate the relationship between social media marketing and customer loyalty. Psychological distance moderates the relationship of social media marketing activity and purchase intention. Hypermarkets are encouraged to develop a strategic social media marketingto increase customers intention to purchase and in the long run will enhance customer loyalty.